IDENTIFIKASI TELUR CACING NEMATODA USUS PADA SISWA KELAS 1 DI SDN INPRES ARDIPURA II TAHUN 2018 - Fajar Bakti Kurniawan; Meidy J Imbiri; Yulianus Wima Krisna Alfreda (POLTEKKES KEMENKES JAYAPURA, 2021)
Ascariasis generally infects elementary school-age children. Children with mild infections usually show no symptoms, but severe conditions can cause intestinal manifestations (diarrhea and abdominal pain), general malaise, delays in cognitive development, depending on the physical action. This study aims to identify intestinal nematodes in grade 1 children at SDN Inpres Ardipura II in Jayapura City. The type of research used is descriptive research with a case study design. The population is 1st grader students at SDN Inpres Ardipura II with 35 people. Descriptive data analysis. The results obtained Ascaris lumbricoides 14.3, Trichuris trichiura 0%, and Hookworm 0%.